5PSQ-014 Novel oral anticoagulants vs vitamin K antagonists: a cost analysis. (March 2019) - Tonelli, M; Barila', DA; Caiazza, E; Scaldaferri, M; Cattel, F
Abstract : Background: In elderly patients, anticoagulants are the most commonly implicated medication in emergency department (ED) visits due to an adverse drug event (ADE): 17.6% of all ADE requiring the ED are linked to oral anticoagulant: 50% of them require hospital admission. Purpose: The aim of the study was to assess whether the main reason for hospitalisation is related to ADE of NOACs: to evaluate the potential exposure to drug-drug interactions/assess whether contraindicated drugs have been prescribed in association with NOACs; and evaluate the economic impact associated with NOACs therapy. Material and methods: Data from 2016–2017 were retrieved from administrative and health databases: the File C2 registry which groups all patients admitted to the ED filtered using identified ICD-9-CM codes (International Classification of Diseases) related to ADE possibly induced by anticoagulants; the File F registry, from local health units to identify anticoagulant therapy; and the hospital discharge form (SDO) which stores clinical information about patients. File C2, File F and SDO were matched to estimate costs incurred by the healthcare system: Diagnosis Related Group (DRG) codes were analysed to evaluate the cost/patient. Results: Data of 1867 patients were extrapolated from File C2, matched with File F, through ICD9-CM related to ADE from anticoagulants: 43 patients were selected (median age=80 (σ=12), male:76%). The most frequent diagnoses were: subdural haemorrhage (31%), iron deficiency anaemia and chronic blood loss (22%), subarachnoid haemorrhage (9%) due to Warfarin (75.5%), Dabigatran (8.9%), Rivaroxaban (8.9%). Crossing File C2 and SDO, 62% of patients in treatment with anticoagulants underwent hospitalisation (average duration of 10 days) and 22/43 patients showed potential drug-drug interactions mainly due to Warfarin. The average cost per hospitalisation was significantly greater for patients treated with Warfarin versus NOACs (€900 more).The lower economic impact of cases treated with NOACs versus Warfarin per DRG (€56 154 vs €201, 743) as for admission to the ED (€1894 vs €6, 952) were linked to the minor incidence of serious ADEs. Conclusion: Making a simulation, the potential saving would be proportional to the number of hospitalisations avoided, (€29, 106, 939). Despite the difference in cost of the therapies shifting from AVKs to NOACs, there could be a direct economic saving related to the lower incidence of hospitalization, and indirect from the reduction of ADE. References and/or acknowledgements: No conflict of interest.